An analysis of manual and autoanalysis for submicrosecond parameters in the typical first lightning return stroke - Muhammad Akmal Bahari; Zikri Abadi Baharudin; Tole Sutikno; Ahmad Idil Abdul Rahman; Mohd Ariff Mat Hanafiah; Mazree Ibrahim (Institute of Advanced Engineering and Science, 2021)
The mechanism on how lightning detection system (LDS) operated never been exposed by manufacturer since it was confidential. This scenario motivated the authors to explore the issue above by using MATLAB to develop autoanalysis software based on the feature extraction. This extraction is intended for recognizing the parameters in the first return stroke, and compare the measurement between the autoanalysis software and the manual analysis. This paper is a modification based on a previous work regarding autoanalysis of zero-crossing time and initial peak of return stroke using features extraction programming technique. Further, the parameter on rising time of initial peak is added in this autoanalysis programming technique. Finally, the manual analysis using WaveStudio (LeCroy product) of those two lightning parameters is compared with autoanalysis software. This study found that the autoanalysis produce similar result with the manual analysis, hence proved the reliability of this software.